𝒥ℋℛ-Operator Pairs in C*-Algebra-Valued Modular Metric Spaces and Related Fixed Point Results with Application. (10th December 2018) - Moeini, Bahman; Ansari, Arslan Hojat; Park, Choonkil
Abstract: In this paper, we introduce and define a concept ofJ H R -operator pair as a pair of non-commuting mappings in a C *-algebra-valued modular metric space. Next, some common fixed point theorems are established for such mappings. Also, to support and elaborate our results, some examples are given and an application is provided for a system of integral equations.